Rheological and tribological evaluation of friction modifiers for wheel‐rail applications. (3rd June 2022) - Leiva‐Mateus, Jairo Eduardo; Santa‐Marín, Juan Felipe; Buitrago‐Sierra, Robison; Mesa Grajales, Dairo Hernán; Geffroy, E.
Abstract: Friction modifiers (FM's) are substances deliberately applied to the top‐of‐the‐rail in the field in order to control the traction coefficient. In this work, two FM's, a commercial (FM1) and a custom‐made (FM2), and a gauge lubricant (CGL) were evaluated in the laboratory using rheological and tribological tests. Two rheological tests were done: oscillatory (frequency and strain sweeps) and flow tests (viscosity vs. shear rate). Tribological tests were done in a twin disk machine to obtain the traction coefficient under different slip values. Retentivity tests were also done in the same machine. Several physical–chemical tests were also done to characterise the products. The results of rheological tests showed that there are notable differences that can influence the performance of FMs. From the studied materials, the FM2 product tends to be more viscous even for high‐shear rates. The tribological tests showed that the traction coefficient is different for all the studied materials and changes from 0.15 to 0.45 depending on the creepage. The retentivity of FM2 is 1.9 times higher than FM1. The results show a good correlation between the rheological behaviour and the coefficient of traction and retentivity.